Metal oxide ion-gated transistors: A perspective on in operando characterizations and emerging Li-ion-based applications - da Silva Neres, Lariel Chagas [UNESP]; Camargo, Luan Pereira; Azari, Ramin Karimi; Garza, José Ramón Herrera; Soavi, Francesca; Barbosa, Martin Schwellberger; Santato, Clara (Springer Nature, 2023)
In this Prospective, we discuss how ionic media interfaced to metal oxide (MO) semiconducting thin films can modulate their electronic conductivity. From in situ diagnosis tools to monitor the state-of-health of Li-ion batteries, to synaptic transistors where ion diffusive dynamics governs short-term and long-term plasticity, technologies based on ionic medium/MO interfaces are emerging, strongly benefitting from advanced nanoscale resolved scanning probe techniques and computational chemistry. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Computation/computing; Devices; Electrical properties; Energy storage; Neuromorphic; Operando